عوامل البيئة الاجتماعية للغة العربية في دعم مهارة الكلام - Makin, Mohammad Makinuddin; Audry Ayuningrum Zid Izzaty Hilmiyah; Qurrota A’yun (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2026)
This study aims to analyze the social environment factors of the Arabic language in supporting the speaking skills of female students at Mambaus Sholihin Islamic Senior High School in Gresik, and to identify the students’ responses toward the Arabic social environment within the boarding school. The study focuses on factors that contribute to the formation of the language environment, such as the use of Arabic in daily activities, interaction among students, and the role of supervisors and language programs in developing speaking skills. The researcher used a qualitative method with a descriptive study approach. The research was conducted within the students’ social environment in the boarding school. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing and verification techniques in order to obtain a comprehensive description of the role of the social environment in supporting the students’ speaking skills. The results of the study showed that the Arabic social environment in the boarding school significantly supports the students’ speaking skills through the implementation of Arabic Language Week, language regulations, and supporting programs such as daily conversations, vocabulary training, and speech practice. The study also found that social interaction among students and the role of supervisors encourage the students to continuously practice Arabic. The students showed positive responses toward the language environment, although they still faced some difficulties such as limited vocabulary and fear of making mistakes. However, they tried to overcome these challenges through practice and cooperation with their classmates.